2002
DOI: 10.1108/00346650210436253
|View full text |Cite
|
Sign up to set email alerts
|

How do consumers use nutrition label information?

Abstract: Previous studies have shown high levels of self‐reported nutrition label use, yet when tested consumers have difficulty in using label information effectively. Using verbal protocol analysis, this study explored nutrition label use directly, identifying the tasks consumers actually undertake, and how these are used to inform choice. The implications of the findings for labelling policy and nutrition education are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
71
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(75 citation statements)
references
References 5 publications
4
71
0
Order By: Relevance
“…In a study of French consumers' use of nutritional information Mannell et al (2006) found that the majority of the respondents do not read nutrition labels because of lack of interest. After an exhaustive review of European studies Higginson et al (2002) observed that studies of nutrition label use reveal generally low levels of use of the information. They cite studies which indicate that in the UK although 62 percent of consumers are aware of nutrition labels only 22 to 59 percent of adults look for information on nutrition when shopping.…”
Section: Nutritional Information Usementioning
confidence: 99%
See 1 more Smart Citation
“…In a study of French consumers' use of nutritional information Mannell et al (2006) found that the majority of the respondents do not read nutrition labels because of lack of interest. After an exhaustive review of European studies Higginson et al (2002) observed that studies of nutrition label use reveal generally low levels of use of the information. They cite studies which indicate that in the UK although 62 percent of consumers are aware of nutrition labels only 22 to 59 percent of adults look for information on nutrition when shopping.…”
Section: Nutritional Information Usementioning
confidence: 99%
“…Higginson et al 2002). Freckleton (1986) as cited by Higginson et al (2002) found that the most common use of nutritional information is to compare nutrition profiles between two different makes of the same product. Other common uses indicated in this study include finding out how the product fits in with the rest of the diet or meal.…”
Section: Nutritional Information Usementioning
confidence: 99%
“…However, objectively assessed use and understanding appears to be lower (1) . Despite high rates of reported use, Higginson et al (2) found that Scottish shoppers used nutrition labels for only 4 % of food purchases on an everyday shopping trip. This increased to 33 % of products when participants were asked to do a healthy shop.…”
mentioning
confidence: 99%
“…Prior exposure to food labels also limits consumers' information searching and consequently saves them time during food purchase (5) . Previous research has found that consumers tend to read the information that is supplied on food labels without really understanding it, which limits the effective use of food labels (6) . At present, although food labels offer consumers more complete, useful and accurate information than ever before (7) , some research studies state that food labels contain too much information, which makes it difficult for consumers to understand them (4) .…”
mentioning
confidence: 99%